DIGITALIZING DA’WAH AND RELIGIOUS AUTHORITIES IN CONTEMPORARY INDONESIA: After the Fall of Religious Leader - Kurniasih, Apri; Raya, Moch. Khafidz Fuad (Journal of Contemporary Islam and Muslim Societies, 2022)
Abstract: Smartphone technology has evolved into a new da‘wah platform in the contemporary era. The emergence of Islamic applications and social media seems to have created a new form of religious involvement in the public sphere in Indonesia recently. This article examines the ‘Aa Gym’ apps and @aagym as a da’wa media platform launched by a popular preacher, KH. Abdullah Gymnastiar. This study describes how the two platforms serve as media for Islamic da’wah with the jargon of iconic religious figures. Using the case study method, we interviewed 20 users of both platforms and Aa Gym as key informants. The results found that: (1) ‘Aa Gym’ apps had created a new form of religious involvement in the digital media landscape before Aa Gym experienced the destruction of itslife, while @aagym was more in demand by the public after practising polygamy as an effort to revive religious authority which had downfall. (2) these two platforms, as primary needs, consume religion without space and time limits. (3) these two platforms depend on the electability of religious figures in the public sphere. Keywords: Islamic applications, religious authorities, religious leaders, digitalization of da’wah, contemporary